Гідрогеноліз глюкози та фруктози в розчинах гліколів на CuO-MgO-ZrO2 каталізаторі - Sharanda, M.E.; Bondarenko, E.A. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2020)
Ethylene glycol and propylene glycol are important representatives of polyols. On an industrial scale, they are obtained from petrochemical raw materials. Within a decade, significant efforts were made for the producing of polyols from biologically renewable raw materials - carbohydrates. The general trend for carbohydrate hydrogenolysis includes application of liquid-phase process with the use of modified metal-oxide catalysts, at 120-120 ° C and pressure of 3MPa or above. So high pressure is used for the reason to increase hydrogen solubility, and also due to the high partial pressure of low boiling solvents. We supposed that usage of high boiling solvents could allow hydrogenolysis to be performed at the lower pressure. Ethylene glycol and propylene glycol are of particular interest as such kind of solvent since they are both the main products of glucose hydrogenolysis. In this work, the process of hydrogenolysis of glucose and fructose over Cu / MgO-ZrO2 catalyst have been studied at temperature range of 160-200 °C and a pressure of 0.1-0.3 MPa in a flow reactor. The solvents were simultaneously the target products of the reaction - ethylene glycol and / or propylene glycol. Gas chromatography and 13C NMR were used for the reaction products identification. It was found that the solubility of glucose in propylene glycol is 21 % by weight, and in ethylene glycol 62 % by weight. It was pointed out that the process of hydrogenolysis can take place at a pressure close to atmospheric. Under these conditions, the conversion of hexoses reaches 96-100 %. The reaction products are preferably propylene glycol and ethylene glycol. The total selectivity for C3-2 polyols is 90-94 %, that is higher than in the hydrogenolysis of glucose in aqueous solution.